(untitled) (Pedagogy of Higher and Secondary Education, 2006)
The article is devoted to the issue of integrated interdisciplinary future book-design experts training m the higher educational institutions. Such preparation should be earned out through the interrelation of methodical fundamental, professional and special disciplines on a design basis.